Types of foreign direct investment and the informal economy: a cross-national assessment - Li, Ang, author; Roberts, Anthony, advisor; Hastings, Orestes 'Pat', committee member; Weiler, Stephan, committee member (Colorado State University. Libraries, 2024)
How does foreign direct investment (FDI) affect the size of the informal economy? Some argue FDI reduces the size of the informal economy by promoting formal employment, while others contend that it facilitates a 'race to the bottom' and leads to the informalization of work. However, the empirical evidence on the effects of FDI is inconclusive. I suggest that this is attributed to previous studies overlooking the sector-specific effects of FDI on the informal economy. Using panel data of 76 countries between 2000 and 2018, this study examines how FDI inflow into the primary, secondary, and tertiary sector, affects the size of the informal economy and whether these effects are moderated by the development and institutional quality of the recipient countries. It shows that primary-sector FDI reduces informal economy in the Developed Countries while increasing informal economy in the Less Developed Countries. This could potentially be explained by the finding that institutional quality suppresses the positive effect of primary-sector FDI. Although I did not find statistically significant results of the impact of secondary- and tertiary-sector FDI, this limitation might be resolved in future study when industry-level FDI data becomes available. Overall, my findings suggest that the impact of FDI on the size of informal economy are heterogenous and can be better explained by the structure rather than the overall magnitude of FDI.
Keywords: globalization; foreign direct investment; informal economy